Novel fusion tags for protein production, purification and research applications - HALAWA, MOHAMED (2020)
Soluble production of recombinant proteins is required for the study of structure and function of these proteins as well as for future therapeutic applications. Unfortunately, many proteins have a propensity to be expressed as insoluble proteins when expressed in a heterologous host, including Escherichia coli. The use of solubility tags is one of the strategies to overcome this difficulty.